2015
DOI: 10.1002/ase.1559
|View full text |Cite
|
Sign up to set email alerts
|

Current integration of dissection in medical education in Australia and New Zealand: Challenges and successes

Abstract: The reduced use of dissection associated with the introduction of integrated systems problem-based learning curricula, graduate-entry programs and medical school expansion is a frequent topic of discussion and debate in modern medical training. The purpose of this study was to investigate the impact of these changes to the medical education landscape, by looking at the current utilization and integration of dissection in medical schools, in Australia and New Zealand. A survey and an invitation to participate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…The main benefits to participation in dissection electives were related to learning style, group-work, and knowledge development. The positive notions regarding learning style and teamwork represent benefits attributed to cadaveric dissection described elsewhere (Patel and Moxham, 2008;Kerby et al, 2011;Davis et al, 2014;Bouwer et al, 2016). Notably, these benefits are not easily captured by conventional examinations.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The main benefits to participation in dissection electives were related to learning style, group-work, and knowledge development. The positive notions regarding learning style and teamwork represent benefits attributed to cadaveric dissection described elsewhere (Patel and Moxham, 2008;Kerby et al, 2011;Davis et al, 2014;Bouwer et al, 2016). Notably, these benefits are not easily captured by conventional examinations.…”
Section: Discussionmentioning
confidence: 93%
“…This de‐emphasis of cadaveric dissection in medical schools has been described in the United States (Drake et al, ), Canada (Ovsenek, ), the United Kingdom (Chapman et al, ), Europe (Pais et al, ), and Australia and New Zealand (Craig et al, ; Moscova et al, ; Bouwer et al, ). Notably, this trend is common to both undergraduate entry medical schools (Ovsenek, ) as well as medical schools where graduate‐level entry is more common (Craig et al, ; Bouwer et al, ). In both cases, there appears to be increased reliance on previously dissected cadaveric material (prosections).…”
Section: Introductionmentioning
confidence: 94%
“…Despite the historical prominence of dissection in medical education, the rationale for its use as a teaching method has stemmed from tradition, rather than a demonstrated impact on learning outcomes [ 28 , 29 ]. A recent survey of Australian medical faculties revealed that dissection is still available in at least 12 of the 20 medical schools with a graduating cohort in 2015 [ 30 ], coinciding with a trend towards increasing use of alternative teaching methods over the past two decades [ 7 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, an impressive number of alternative methods of learning anatomy approach. Sometimes, dissection is being totally replaced by the use of new technologies, or changes in the medical curriculum leave a short amount of time for dissection, according to Bouwer et al and to Whelan et al 19,20 Every method has its unique features and advantages, mostly because of opportunities of vital study, visual quality, and ethical aspects. However, according to Estai et al, who composed a comparative analysis of all teaching and learning techniques that are used in medical universities nowadays, these methods have serious disadvantages in comparison to dissection.…”
Section: Discussionmentioning
confidence: 99%